Student Motivation for Choosing KPI Study Program at FDIK IAIN Padangsidimpuan - Nurfitriani M. Siregar (Hikmah, 2022)
This study discusses the motivation of students to choose the KPI study program at FDIK IAIN Padangsidimpuan. The research method used is descriptive qualitative. The results of research conducted by researchers from data obtained in the field, that the factors that influence students to choose the Islamic Broadcasting Communication Study Program, Faculty of Da'wah and Communication Studies are influenced by internal factors and external factors. The internal factors that influence the motivation of students to choose the Islamic Broadcasting Communication Study Program are the aspiration to become a journalist, broadcaster and public speaking believer, wanting to deepen their religious knowledge and develop their interests and talents from within, and external factors that influence the motivation of students to choose the Study Program. Islamic Broadcasting Communication is the encouragement of parents who want to send their children to universities with Islamic nuances, the encouragement of their friends and relatives and even their ustadzah or teachers when they want to choose a study program formation, the costs are relatively cheap and affordable for parents to put their children in college, this is a which is the reason students are motivated to choose the Islamic Broadcasting Communication Study Program.Keywords: motivation